Signing Auditor-Specific Characteristics And Audit Report Lag: A Research From Turkey - (:unkn) unknown (My University, 2018)
The purpose of this paper is to examine the effect of signing auditor-specific characteristics on the audit report lag using 968 firm-year observations from Borsa İstanbul in the period 2008-2013. The main findings indicate that the gender and education level of signing auditor have a positive effect on audit report lag. Also big4 audit firms in Turkey encourage auditees to present financial statements timely and they play a substantial role in the reporting. Audit opinion directly affects audit report lag. Firm performance and firm age inversely affect audit report lag. Moreover, big 4’s female signing auditors lead to more audit delay. The higher educational level of signing auditors leads to more audit report lag. Signing auditors who hold master’s or Ph.D. degrees and also female signing auditors are associated with more audit report lag in firms audited by big4 and non-big4 firms.
Signing Auditor-Specific Characteristics And Audit Report Lag